Brand Trust, Brand Image, And Relationship Quality On Brand Loyalty In The Context Of Halal Product - Utami, Budi (SEIKO : Journal of Management & Business, 2023)
The purpose of this research is to evaluate the development of halal food and beverage products. The variables in this study are brand trust, brand image, relationship quality to brand loyalty. The population of this research is all MSME food products and at least halal in Malang City. The sample of this research is 303 halal food and beverage products. This research analysis technique uses SmartPLS. The results of this study indicate that the first hypothesis, brand trust has a positive and significant effect on brand loyalty. The second hypothesis, brand trust has a positive and significant effect on relationship quality. The third hypothesis, brand image has a positive and significant effect on brand loyalty. The fourth hypothesis, brand image has a positive and significant effect on relationship quality. The fifth hypothesis, relationship quality has a positive and significant effect on brand loyalty. The sixth hypothesis, brand trust has a positive and significant effect on brand loyalty mediated by relationship quality. The seventh hypothesis, brand image has a positive and significant effect on brand loyalty mediated by relationship quality. Therefore, it can be concluded that all variables explain the existence of halal regulations as a factor influencing brand trust and brand image can convince customers to maintain good quality relationships and become loyal customers of halal food and beverage products. The limitation of this research is the Malang City area, it is expected to expand the area related to the development of halal product labels in Indonesia.